Risk score model for predicting mortality among patients with lung cancer - Huh, Youn; Kim, Hae-Rim; Kim, Hwa Jung; Son, Ki Young (Frontiers in Medicine, 2024)
Background: To develop an accurate mortality risk predictive model among patients with lung cancer. Methods: The development cohort included 96,255 patients with lung cancer aged ≥19 years, who underwent a Korean National Health Insurance Service health check-up from 2005 to 2015. The validation cohort consisted of 18,432 patients (≥19 years) with lung cancer from another region. The outcome was all-cause mortality between January 1, 2005, and December 31, 2020.Results: Approximately 60.5% of the development cohort died within a median follow-up period of 2.32 (0.72-5.00) years. Risk score was highest in participants aged ≥65 years, followed by those who underwent treatment, had a history of emergency room visits, and were current smokers. Participants treated by surgery had the lowest risk score, followed by combined surgery and chemotherapy, combined surgery and radiation therapy, women, and regular exercisers. The C statistic in the development and validation cohorts was 0.78 (95% confidence interval: 0.77-0.78) and 0.81 (95% confidence interval: 0.78-0.84), respectively.Conclusions: Advanced age, lung cancer stage, and treatment type were strong risk factors of mortality in lung cancer patients, while women sex and exercise were preventive factors. These will aid in the prediction of mortality and management of lung cancer patients.